2018
DOI: 10.2807/1560-7917.es.2018.23.23.1800287
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of an outbreak of gonorrhoea with high-level resistance to azithromycin in England, November 2014‒May 2018

Abstract: Between November 2014 and May 2018, 118 laboratory-confirmed cases of high-level azithromycin resistant Neisseria gonorrhoeae were identified in England. Cases emerged among heterosexuals in Leeds but spread across England and into sexual networks of men who have sex with men as the outbreak progressed. The few epidemiological links identified indicate substantial under-diagnosis of cases and this, along with the upturn in cases in 2017, highlights the difficulties in controlling the outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…DNA sequence analysis revealed that all 14 isolates harbored the mosaic-mtr and the A2059G mutation in all four copies of their 23S rRNA gene. While investigators from many countries have reported on the A2059G mutation or the mosaic-mtr, none described these two haplotypes together (5,10,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The 14 isolates in this study are the first known isolates to have possessed both the A2059G mutation and the mosaic-mtr.…”
Section: Resultsmentioning
confidence: 78%
“…DNA sequence analysis revealed that all 14 isolates harbored the mosaic-mtr and the A2059G mutation in all four copies of their 23S rRNA gene. While investigators from many countries have reported on the A2059G mutation or the mosaic-mtr, none described these two haplotypes together (5,10,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The 14 isolates in this study are the first known isolates to have possessed both the A2059G mutation and the mosaic-mtr.…”
Section: Resultsmentioning
confidence: 78%
“…These issues are further explored in Chapter 6. The outbreak investigation of high level azithromycin resistant isolates in England has continued to persist over a number of years (192). Although it emerged within young heterosexuals, no specific risk factors were identified that could explain the initial outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…It subsequently spread to other areas in England as well as making its way into the MSM population. The control of these STI-associated outbreaks often includes partner notification but had limited effectiveness in the investigation (192). There were very little epidemiological links between cases, with no association by specific venues, online dating applications or common education establishments, suggesting that undiagnosed infections were a large contributor to the persistence of this outbreak (192).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations